Molecular Phylogeny of Agrioglypta Meyrick and Talanga Moore (Lepidoptera: Crambidae; Spilomelinae) Inferred from Nuclear EF-1a Gene - HARI SUTRISNO (HAYATI Journal of Biosciences, 2005)
The phylogeny of the two closely- related genera, Agrioglypta Meyrick and Talanga Moore, was inferred from nucleotide sequence variation across a 973-bp region in the nuclear elongation factor-1 (EF-1) gene. Seven species representing the two genera and two outgroup species (Feltia jaculifera Guene and Metallarcha aureodiscalis Meyrick) were analyzed. The results showed the averages of the p-distances in the comparisons between species within genus and between species belonging to other different genera were 3.5% and 4.9%, respectively. EF-1 gene had almost reached saturation at the level of the divergence of these two genera. The phylogenetic analysis using MP and NJ methods showed that each genus was found to be a monophyletic group and the species relationships within each genus were almost consistent as well. A. eurytusalis is the basal species in the genus Agrioglypta. In the genus Talanga, T. sabacusalis lied in the basal node and T. tolumnialis was found to be sister group of T. sexpunctalis.